Cisplatin vestibulotoxicity: a current review - Fleihan, Tamara; Nader, Marc Elie; Dickman, J. David (Frontiers in Surgery, 2024)
Cisplatin, a commonly used chemotherapy drug, is well-established for its ototoxic effects, primarily attributed to the damage it inflicts on cochlear hair cells. However, its impact on the vestibular system remains inadequately understood. Here, we provide a comprehensive review of existing literature concerning cisplatin-induced vestibulotoxicity. Animal studies have shown that cisplatin induces a vestibular hair cell loss that is dose-dependent, with the severity of damage also varying according to the route of administration. Notably, intratympanic and systemic injections in animal models have manifested significant damage primarily to utricular hair cells, with a lesser degree of damage observed for the other vestibular end organs. The underlying mechanisms of cisplatin induced vestibular hair cell loss include apoptosis, oxidative stress, and inflammatory cytokines. Several protective agents, such as Pifithrin-α, DAPT, Ginkgolide B, and heat shock proteins, have demonstrated efficacy in inhibiting cisplatin-induced vestibular damage in preclinical studies. Human clinical findings indicate that cisplatin treatment can cause vestibular dysfunction, characterized by symptoms ranging from transient dizziness to persistent vertigo. Challenges in diagnosis, including the limited utilization of comprehensive vestibular testing for many patients, contribute to the variability in reported outcomes. Cisplatin-induced vestibulotoxicity is a significant complication of chemotherapy, necessitating further research to understand its mechanisms and to improve diagnosis and management, ultimately aiming to enhance the quality of life for cancer patients undergoing cisplatin therapy.